Methods Of Teaching Creative Writing Among Educators And Literary Psychologists/ أساليب تدريس الكتابة الإبداعية بين التربويين وعلماء نفس الأدب - Almugim, Tarig Muhmmad (Ijaz Arabi Journal of Arabic Learning, 2023)
This research aims to describe methods of teaching creative writing skills, and efforts are made to reveal the most prominent teaching methods. The research method used is qualitatively from creative writing classes, using teachers and students as data sources. The results of this research are studies focused on specific methods for creative writing. In contrast, in the classroom, without paying attention to studies related to observing the creators reveal new additions to their first creative attempts, these studies are similar to the efforts of psychologists when they studied the work mechanisms of creative people and artists. Naturally, such efforts must be carried out by all parties of the educational institution, starting with the curricula and passing through the teacher, then the student and his family members, by following up on the changes and additions that his creativity is going through in accordance. The known stages of creativity (preparation- the stage of incubation and latency - the stage of illumination - verification - the stage of determination and perseverance) Despite the challenges surrounding this follow-up, its impact is praiseworthy and significant on the individual and society. Also, monitoring the student’s written creativity at various stages does not negate the strategies used in teaching creative writing in the classroom, as it is the first stage of discovering the creative student.